Speech Prosody 2016 2016
DOI: 10.21437/speechprosody.2016-72
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prosodic structure and information density on vowel space size

Abstract: We investigated the influence of prosodic structure and information density on vowel space size. Vowels were measured in five languages from the BonnTempo corpus, French, German, Finnish, Czech, and Polish, each with three female and three male speakers. Speakers read the text at normal, slow, and fast speech rate. The Euclidean distance between vowel space midpoint and formant values for each speaker was used as a measure for vowel distinctiveness. The prosodic model consisted of prominence and boundary. Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…In contrast to Schulz et al (2016) and Aylett and Turk (2006), we found a positive but non-significant effect of stress on vowel dispersion. This difference might be due to the weak positive correlation between surprisal and stress (r = 0.23).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to Schulz et al (2016) and Aylett and Turk (2006), we found a positive but non-significant effect of stress on vowel dispersion. This difference might be due to the weak positive correlation between surprisal and stress (r = 0.23).…”
Section: Discussioncontrasting
confidence: 99%
“…Effects for both variables cannot be fully separated in a statistical model. In addition, Schulz et al (2016) analyzed only five languages of the BonnTempo corpus, DEU, CES, POL, FIN, and FRA. The present study also includes (American) English, a language which shows a relatively strong correlation between surprisal and vowel dispersion [r = 0.26, t (558) = 6.39, p < 0.001].…”
Section: Discussionmentioning
confidence: 99%
“…Texts of more recent scientific articles typically contain a higher average information density than texts from earlier periods (Degaetano-Ortlieb et al an influence on the expectations of text users with regard to upcoming linguistic elements based on previous experience with similar texts. The effect of information density on choices between different types of phonological or syntactic alternatives (e.g., the preferences of full or contracted auxiliaries or the use of complement clauses with and without the complementizer 'that') has been addressed by various scholars, especially in psycholinguistic studies (Demberg & Keller 2008;Hale 2001;Levy 2008) and recently also in corpus-linguistic studies (e.g., Degaetano-Ortlieb & Teich 2017; Schulz et al 2016;Zimmerer et al 2017). However, morphological structures within complex lexemes with the potential to combine various lexical morphemes still remain to be studied.…”
Section: Rationale and Hypothesesmentioning
confidence: 99%
“…Conventions and rules of prominence, as well as predictability of linguistic units are language-specific. Also, the influence of information density on phonetic encoding density seems to be language-specific [4].…”
Section: Introductionmentioning
confidence: 99%
“…Phonetic structures in high ID contexts are increased, while reduced phonetic structures are usually found in low ID contexts. Easily predictable vowels are less dispersed than vowels that are less predictable [3,4]. Vowel dispersion is defined as the Euclidean distance between the average centre of the vowel space and formant values for each vowel [5].…”
Section: Introductionmentioning
confidence: 99%